2010
DOI: 10.1111/j.1939-165x.2009.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of albuminuria and its relationship with blood pressure in dogs with chronic kidney disease

Abstract: UAC ratio was higher in hypertensive than in normotensive dogs with CKD. Tests designed to detect microalbuminuria may be useful for hypertensive dogs with CKD and a UPC < or = 1.0 to detect the onset and magnitude of albuminuria. Once macroalbuminuria is overt, the UPC ratio itself can be used for the same purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 39 publications
2
39
1
15
Order By: Relevance
“…There are discrepancies in the literature regarding the percentage of dogs with kidney disease that develop systemic hypertension (MICHELL et al, 1997;JACOB et al, 2003;POLZIN, 2012). Such divergences may be due to different stages as well as to the nature of renal disease, because glomerulopathies are more likely to cause hypertension than tubulointerstitial diseases (CORTADELLAS et al, 2006;BACIC et al, 2010). There is only one previous study that evaluated the prevalence of hypertension in dogs with leishmaniosis, which revealed that 61.5% of the dogs with glomerular disease were hypertensive.…”
Section: Introductionmentioning
confidence: 89%
“…There are discrepancies in the literature regarding the percentage of dogs with kidney disease that develop systemic hypertension (MICHELL et al, 1997;JACOB et al, 2003;POLZIN, 2012). Such divergences may be due to different stages as well as to the nature of renal disease, because glomerulopathies are more likely to cause hypertension than tubulointerstitial diseases (CORTADELLAS et al, 2006;BACIC et al, 2010). There is only one previous study that evaluated the prevalence of hypertension in dogs with leishmaniosis, which revealed that 61.5% of the dogs with glomerular disease were hypertensive.…”
Section: Introductionmentioning
confidence: 89%
“…Hypertension has been linked to target organ damage in dogs, and has been suggested to contribute to stroke2 and albuminuria5 in Greyhounds. High SP was associated with more severe proteinuria and renal histologic lesions in dogs with surgically induced renal failure30 and with naturally occurring chronic kidney disease 31. While not directly correlated with SP, 50% of the Greyhounds in this study had urinary albumin concentrations >1.0 mg/dL and 10% had concentrations >2.5 mg/dL, considered to be significant albuminuria.…”
Section: Discussionmentioning
confidence: 53%
“…Hypertension could contribute to progression of renal damage, causing glomerulosclerosis as proteinuria and glomerular disease may occur in the majority of dogs with chronic kidney disease and systemic hypertension (Schellenberg et al 2008, Bacic et al 2010, Reusch et al 2010.…”
Section: Discussionmentioning
confidence: 99%